Informacinės technologijos: prekybos tendencijos - Burinskienė, Aurelija (Information & Media, 2014)
Informacinių technologijų taikymo sąlygomis verslo subjektams atsiveria iš esmės naujos galimybės. Šios technologijos sudaro palankesnes sąlygas plėtoti veiklą tarptautinėse rinkose, diegti naujus verslo modelius, didinti verslo perspektyvas. Šiuolaikinės globalizacijos sąlygomis informacinės technologijos tapo esminiu raidos ir plėtros veiksniu tiek įmonių veikloje, tiek apskritai prekyboje. Ši tematika nuolat gvildenama mokslinėse publikacijose. Tačiau atlikta žinomų pasaulio leidyklų mokslinės literatūros analizė parodė, kad stokojama mokslinių apibendrinimų, skirtų informacinių technologijų prekybos tematikai. Kaip rodo empiriniai tyrimai, ši tematika turi būti nagrinėjama per informacinių technologijų kūrimo ir tobulinimo prizmę. Straipsnyje pateikiama praktinė prekybos sąsajumo su informacinių technologijų kūrimu ir tobulinimu analizė, nagrinėjami pokyčiai, siejami su investicijomis į informacines technologijas.Pagrindiniai žodžiai: informacinės technologijos, informacinių technologijų kūrimas ir tobulinimas, prekybaInformation technologies: trade tendenciesAurelija BurinskienėSummaryDuring empirical research, the author identified that the money spent for the development of information technologies highly affect the foreign expansion of trade in United Kingdom and Germany.It is also noted that investments in information technologies result gradually blurring the boundaries between trading and manufacturing businesses and other changes. Both production and trading enterprises, in addition to their main business, are engaged in selling or producing activities. Such leads to the new forms of business practices.Investments in information technology also affect changes in the distribution channel. Under the conditions of technology usage, the flows of information, products, and money becoming more frequent between distribution channel partners.The article discloses theoretical and practical aspects of trade in information technologies. In the paper attention is given to export of IT services and licenses; also to investments into IT development and research activity; as well as the effect of these investments to the development of foreign trade.The research is splitted into two parts. The results of the study, which was dedicated to export and import ratio study, showed that the export of IT licence is higher than import in EU, US, and Japan.The second part of the study was given to the dependence between research and development activity and the development of international trade analysis. Results showed that the investments into information technologies, research and experimental work positively affect the exporting ability of enterprises.